COVID-19 during pregnancy: vertical transmission, diagnosis and maternal-fetal complications - Moukit, Mounir; Ouardi, Assia El; Babahabib, Abdellah; Hassani, El Mehdi El; Kouach, Jaouad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
The current pneumonia outbreak of COVID-19 has been declared a pandemic by the World Health Organization on March 11, 2020. With its indiscriminate spread across continents, authors are likely to see women with COVID-19 canvassed across all trimesters of pregnancy. To date, few reports have provided information about this disease in pregnant patients. Authors conducted a literature review to summarize the results concerning intrauterine transmission, diagnostic challenges and maternal-fetal outcomes of pregnant women with COVID-19 pneumonia.